The Effect of Nimodipine towards Calcium Ion (Ca2+) Expression in SH-SY5Y Neuron Cell Culture Exposed By Chronic Hyperglycaemia - Shahdevi NK (Journal of Global Pharma Technology, 2020)
Diabetic neuropathy is a complication of diabetes mellitus which forms clinical or subclinical that affecting the peripheral nervous system. In diabetes condition, changes in calcium ion signalling contribute to the development of distal symmetrical sensorimotor polyneuropathy (DSN) and pain. Increasing of cytosolic calcium involved in neuron degenerative and cell apoptotic process. This study discusses the effect of nimodipine, an L-type calcium channel blocker, on calcium ions (Ca2+) in SH-SY5Y culture cell line exposed to chronic hyperglycemia. This study, using in vitro research model. Before measuring calcium ions (Ca2+), the study sample was divided into three groups with 6 days of glucose administration; 5 mM noromoglycemia, 25 mM hyperglycemia, and 50 mM hyperglycemia. Each group was given different treatment; without nimodipine, nimodipine 10 nM and nimodipine 100 nM for 30 minutes, then proceed to observe of Ca2+ concentration parameters by fluo-3 dye using confocal laser scanning microscopy (CLSM). The results showed that higher dose of glucose could increase the calcium ion significantly. The administration of nimodipine at 10 nM and 100 nM doses significantly reduced calcium ions in the 25 mM and 50 mM glucose groups. In the 5 mM glucose group with administration of 10 nM and 100 nM nimodipine, Ca2+ has shown increased. The conclusion of this study is the administration of nimodipine could decrease calcium ions in SH-SY5Y cells exposed to chronic hyperglycemia. Keyword: Nimodipine, Calcium Ion (Ca2+), Diabetic Neuropathy.